2022
DOI: 10.1590/s0004-2803.202200001-21
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic, Prebiotic or Symbiotic Supplementation Impacts on Intestinal Microbiota in Patients With Nonalcoholic Fatty Liver Disease: A Systematic Review

Abstract: Background Supplementation with probiotics, prebiotics and symbiotics has shown positive effects on clinical markers and risk factors for non-alcoholic fatty liver disease (NAFLD). Objective To evaluate the effect of supplementation with probiotic, prebiotic or symbiotic on intestinal microbiota in NAFLD patients. Methods Two investigators conducted independently search for articles in the Medline databases, via PubMed, Web of Science, Embase, Scopus, Lilacs, Central Cochrane Library, Clinical Trials.gov and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Human studies have shown an increase in the relative abundance of Proteobacteriaceae (Proteobacteria), Enterobacteriaceae, Escherichia, and Doreia in NAFLD patients, while Rumenococcaceae, Faecalibacterium Praeplastrum (Ruminococcaceae), Faecalibacterium Prausnitzii, Coprococcus, Eubacterium, Prevotella, and Anaerospacteracter were found to decrease in relative abundance [107][108][109][110]. In rodent trials, individuals with NAFLD showed a significant increase in Firmicutes abundance, while Bacteroidetes were reduced [111]. Dysbiosis can lead to NAFLD through various pathways [112].…”
Section: Gut Dysbiosis and Gut-liver Axismentioning
confidence: 99%
“…Human studies have shown an increase in the relative abundance of Proteobacteriaceae (Proteobacteria), Enterobacteriaceae, Escherichia, and Doreia in NAFLD patients, while Rumenococcaceae, Faecalibacterium Praeplastrum (Ruminococcaceae), Faecalibacterium Prausnitzii, Coprococcus, Eubacterium, Prevotella, and Anaerospacteracter were found to decrease in relative abundance [107][108][109][110]. In rodent trials, individuals with NAFLD showed a significant increase in Firmicutes abundance, while Bacteroidetes were reduced [111]. Dysbiosis can lead to NAFLD through various pathways [112].…”
Section: Gut Dysbiosis and Gut-liver Axismentioning
confidence: 99%
“…Other reviews evaluated the effectiveness of prebiotics or probiotics alone [ 24 , 25 , 26 , 27 ]. Only two reviews compared the effects of probiotics, prebiotics and synbiotics on liver enzymes, but not on other risk factors associated with NAFDL and NASH [ 23 , 28 ]. Souza et al [ 28 ] also performed a review comparing the effects of probiotics, prebiotics and synbiotics on NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Only two reviews compared the effects of probiotics, prebiotics and synbiotics on liver enzymes, but not on other risk factors associated with NAFDL and NASH [ 23 , 28 ]. Souza et al [ 28 ] also performed a review comparing the effects of probiotics, prebiotics and synbiotics on NAFLD. Nevertheless, only four trials were included in the review.…”
Section: Introductionmentioning
confidence: 99%
“…Eles ajudam a criar uma camada protetora entre parede intestinal e bolo alimentar, a impedir a constipação e a tratar diversos tipos de diarreia. Os probióticos também auxiliam os movimentos peristálticos,(SOUZA, 2022).Bactérias intestinais podem produzir neurotransmissores como acetilcolina, GABA e serotonina. Os baixos níveis de serotonina estão associados a um maior risco de problemas de sono e depressão e estudos o intuito de repor a microbiota intestinal.…”
unclassified